Emperor Leopold I (1640-1705) His Internal and External Policy (Damascus University Journal of Historical Studies, 2023)
Enemies from the East and West had Lurked in the Holy Roman Empire of "the German Nation" for a long time throughout the reign of the Emperor (Caesar) Leopold I. As a result, his life was fated to be surrounded by wars;  in the West, his wars were with his relative the King of France, Louis XIV, and in the east his wars with the Ottoman Empire. However, using his Political cleverness,  he was able to weave military and strategic alliances with: the princes of his Empire, and the Papacy, and the king of Poland which led to the defeat of the Ottomans before the walls of Vienna in 1683. The Emperor had fiercely defended his interests in the Empire and in Spain against his archenemy Louis XIV, and conducted a number of strategic alliances to this aim. On the other hand, he skillfully and pragmatically managed the internal affairs of his empire. He granted the King of Brandenburg the independence in  1700 and acknowledged him to bring to light the Kingdom of Prussia, which was planned to play a prominent role in the history of Europe. Despite all the external dangers and internal problems, Emperor (Caesar) Leopold I excelled in the field of music and composition, along with giving culture the best attention. Moreover, he established many universities presenting to the people of his empire a large number of achievements, which was enough reason for his people to love and immortalize him.
Keywords: Emperor (Caesar) Leopold I; King Louis XIV; Sultan Mohammed IV; The Holy Roman Empire of